Lipomatous variant of angiomyofibroblastoma-like tumor in male through fine needle aspiration: “False positive just is in the eye of the beholder” - Canberk, Sule (Citotech Online - Case Review, 2015)
Angiomyofibroblastoma-like tumor of male is an extremely rare benign mesenchymal tumor. It commonly occurs in middle-age and is mainly localized in the inguinoscrotal region. It is originated from perivascular stem cells and has the capacity of lipoid and myofibroblastic differentiation that may allow the observation of lipomatous differentiation. We report a case of lipomatous variant of angiomyofibroblastoma-like tumor of male using fine needle aspiration biopsy from the scrotal region of a 53 years-old man. Differential diagnosis could be a real bane for the pathologist in this particular variant. This diagnose should be kept in mind to prevent overlapping with the malignant lipomatous tumors.